Exploring a Mathematics Teacher’s Conceptions of Infinity: The Case of Louise - Irving Aaron Diaz-Espinoza; José Antonio Juárez-López; Estela Juárez-Ruiz (Universitas Tidar, 2023)
Several papers studied infinity from the difficulties that students and teachers show in developing the concept. For this study, it was considered the analysis of the equality 0.999 … = 1. Mainly, this research aims to show that a mathematics teacher presents erroneous conceptions just like a student; that is, both students and teachers have the same difficulties in the concept of infinity. To this aim, a semi-structured interview was conducted with an in-service mathematics teacher in Tlaxcala, Mexico. The purpose of this research is to exhibit a high school math teacher’s misconceptions about the concept of infinity. In general, misconceptions found here can be divided into four groups: without a clear picture of the concept of infinity, an infinite periodic decimal number cannot be a representation of a finite number, a decreasing infinite sum cannot lead to a finite number and an infinite process is limited in real life is finite and has ended. The results obtained were compared with those already available in references about the difficulties with students and teachers, finding that the results shown here are like those reported in the literature. This highlights the need to overcome the teacher’s conceptions of infinity in future research.